The Heuristic Potential of the Synergetic Paradigm in Law and Criminology - Filipenko, Nataliia; Lukashevych, Serhii; Danets, Serhii (Archives of Criminology and Forensic Sciences, 2023)
Abstract. This article delves into the conceptual foundations, perspectives, and ideas surrounding the essence of an interdisciplinary (multidisciplinary) scientific direction termed “synergetics”. The authors posit that synergetic concepts are valuable in criminology both for elucidating the causes of criminal behavior and for structuring systems of crime prevention and legal influence. From a synergetic standpoint, randomness can serve not merely as a manifestation of necessity but also as its complement. In explaining the roots of criminality, employing the principle of subordination in criminology could also prove beneficial. When understanding the causal nexus of criminality, it becomes pivotal to identify overarching indicators that play a primary, defining role within the complex.